Validation of Analytical Method of Testing Cefotaxime Sodium in Injection Powder Preparation by High-Performance Liquid Chromatography - Aneu Aryani Pratiwi; Dikdik Mulyadi; Devi Indah Anwar (Berkala Ilmiah Kimia Farmasi, 2023)
Cefotaxime sodium was an antibiotic drug included in the third-generation cephalosporin group. The aim of this research was to validate the method used for the analysis of cefotaxime sodium injection powder using HPLC. Parameters performed in this study included system suitability, selectivity, linearity, accuracy, precision, robustness, Limit of Detection (LOD), and Limit of Quantitation (LOQ). In this study, the mobile phase used was phosphate buffer pH 6,25 with methanol in the ratios of (30:70), (40:60), (50:50), (60:40), and (70:30) v/v. The analysis was carried out using a 150 × 4,6 mm 5μm C18 column and phosphate buffer pH 6,25 with methanol (40:60) v/v as a mobile phase with a flow rate of 1 mL/min, and a detector at a wavelength of 235 nm. The results showed that the system suitability test results met the requirements, with a plate number of 2288, a standard deviation of 0,93%, and a tailing factor of 1,3. The linearity results met the requirements of r ≥ 0,999 with LOD and LOQ values of 3,3894 ×10⁻⁴ mg/mL and 1,0271 ×10⁻³ mg/mL, respectively. The accuracy results obtained a recovery value of 99,30% and an RSD of 0,48%. Precision results of repeatability and intermediate precision had RSDs of 0,38% and 0,85%, respectively. Robustness test results obtained a recovery value of 100,25% and an RSD of 0,85%. The results showed that the recovery values (98-102%) and RSD ≤ 1,5% were in accordance with the validation requirements. It was concluded that the validation of the proposed method was recommended and could be used for routine analysis. Keywords:  Cefotaxime Sodium, Method Validation, HPLC